FEARS AND PHOBIAS IN THE PERSON’S «ANXIETY ROW» PHENOMENA STRUCTURE - I. V. Astakhova (Модернизация, инновация, развитие, 2016)
Fear is determined as part of a sequence of so-called «number of anxiety» phenomena (fright – alarm – fear – horror – panics). Phobia isdetermined as alarming upsetting. The origin and development of fears and phobias are examined from the social viewpoint in terms of theinfluence of the «alarm raw» phenomena on the development of both an individual and the whole society.